TO THE QUESTIONNAIRE OF THE DEFENSE OF COMMUNICATION ACTIVITIES IN THE WORK OF THE LAWYER - Kim, K. V. (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2017)
the article notes the growing social need for qualified personnel; Places of possible employment of the graduate of a specialty «Jurisprudence» are specified; the views of individual scientists on the definition of the most important factors of the professional suitability of a lawyer are outlined; it is established that communication is an important and integral part of the work of a lawyer in all its forms.